2005
DOI: 10.1071/sr04095
|View full text |Cite
|
Sign up to set email alerts
|

Soil water repellency under dry and wet antecedent weather conditions for selected land-cover types in the coastal zone of central Portugal

Abstract: This paper reports on the first systematic inventory of soil water repellency in Portuguese coastal dune sand areas. Since water repellency is widely associated with certain vegetation types or individual plant species, this inventory concerned arable land as well as 6 natural and semi-natural land-cover types representative for the vegetation zonation in the study area. Since water repellency further is a feature that commonly varies through time, disappearing when soils become wet, initial sampling was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
7
28
1
Order By: Relevance
“…The hydrophobic nature of charcoal residues might have contributed to the comparatively high erosion rates at the EB site (Malvar et al, 2013;Prats et al, 2014;Shakesby and Doerr, 2006). Not only long unburnt but also recently burnt eucalyptus plantations in the study region have been found to exhibit extreme topsoil water repellency, especially during dry antecedent weather conditions (Keizer et al, 2005(Keizer et al, , 2008. Phenols and alkylphenols were found in all samples, probably originating from phenolic precursors compounds such as lignin, tannin, proteinaceous biomass, and carbohydrates (Tegelaar et al, 1995) or derived from the heat-transformed products of such constituents .…”
Section: Organic Matter Composition In Topsoil and Eroded Sedimentsmentioning
confidence: 96%
“…The hydrophobic nature of charcoal residues might have contributed to the comparatively high erosion rates at the EB site (Malvar et al, 2013;Prats et al, 2014;Shakesby and Doerr, 2006). Not only long unburnt but also recently burnt eucalyptus plantations in the study region have been found to exhibit extreme topsoil water repellency, especially during dry antecedent weather conditions (Keizer et al, 2005(Keizer et al, , 2008. Phenols and alkylphenols were found in all samples, probably originating from phenolic precursors compounds such as lignin, tannin, proteinaceous biomass, and carbohydrates (Tegelaar et al, 1995) or derived from the heat-transformed products of such constituents .…”
Section: Organic Matter Composition In Topsoil and Eroded Sedimentsmentioning
confidence: 96%
“…The approach involves a series of comparisons. A pine and a eucalypt forest stand were selected for study because they had been found to differ substantially in repellency conditions during late summer 2000 (Keizer et al 2005, this issue), with the eucalypt stand presenting a higher overall repellency level as well as a more homogeneous spatial pattern. Within each stand, 2 slopes were selected with contrasting aspects and, in association, somewhat different slope angles.…”
Section: Introductionmentioning
confidence: 99%
“…In the study area, following dry spells and with presence of strong soil water repellency, rainfall events produced negligible amounts of OLF as well-illustrated by the dry events. It is well-established that soil water repellency and its high spatial variability (Keizer et al, 2005a;Leighton-Boyce, 2003;Santos et al, 2013) promote spatially localized infiltration or percolation, with the development of fingered or preferential flow paths, which can explained the observed low production of OLF. Nevertheless, during the dry period, SSF came exclusively from the soil matrix, therefore, the water that infiltrated by preferential paths was reabsorbed by soil matrix.…”
Section: Overland Flowmentioning
confidence: 99%
“…Also saturation-excess OLF can be expected to play an important role in streamflow generation in the study region, especially during the wet winter seasons when soil water repellency tends to be less pronounced Keizer et al, 2005a). Namely, rainfall is rather high in the upper Caramulo Mountains in particular, amounting to over 1400 mm per year, and soils tend to be shallow (Malvar et al, 2013;Shakesby et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation